NEUROCHIPS AND THEIR PROPERTIES - Axmedov Baxriddin Madaminovich; Astonaqulova Kibriyoxon Baxriddin qizi (Web of Journals Publishing, 2024)
This article provides information about the history of the development of neurochips, the Neuralink project, the principles of operation, practical application and their impact on the future of mankind, namely the benefits and dangers.
Keywords: neurochip, interface, artificial intelligence, medical implant, artificial ear (cochlear implant), computer, robot.